Survival Strategy of Family dalam Meraih Generasi Emas Perspektif QS Al-Nisa’ Ayat 9 - M. Ilham; Patma; Muh. Mukmin Passa (Al Iman: Jurnal Keislaman dan Kemasyarakatan, 2026)
This study aims to identify and analyze the survival strategies of Muslim families in facing challenges in the era of globalization, specifically within the context of forming a "golden generation" grounded in religious teachings. Referring to the perspective of QS al-Nisa>’/4:9, this research explores various dimensions of family resilience, such as character building in children, managing moral values, and implementing Islamic principles in daily life. This is a type of library research with a qualitative approach, where the author collects data from various sources, such as books, journals, and other relevant literature. The findings reveal several challenges in achieving a golden generation, including environmental, moral, social, educational, and halal livelihood factors. Therefore, the implementation of the family survival strategy based on QS al-Nisa>’/4:9 encompasses three main aspects: strengthening faith, improving education, and stabilizing the economy. By applying this Survival Strategy, it is hoped to provide guidance for Muslim families in building a solid foundation based on Islamic values, enabling future generations to grow with firm faith, moral integrity, and ethics to meet the challenges of the times. Penelitian ini bertujuan untuk mengidentifikasi dan menganalisis strategi bertahan keluarga muslim dalam menghadapi tantangan di era globalisasi, khususnya dalam konteks pembentukan generasi emas yang berlandaskan ajaran agama. Dengan merujuk pada persfektif QS al-Nisa>’/4:9. Penelitian ini mengeksplorasikan berbagai dimensi ketahanan keluarga, seperti pembinaan karakter anak, pengelolahan nilai moral dan penerapan nilai-nilai ke Islaman dalam kehidupan sehari-hari. Penelitian ini merupakan Jenis penelitian kepustakaan (library Research), dengan metode kualitatif, penulis mengumpulkan data dari berbagai literatur seperti buku, journal dan sumber lainnya yang relevan dengan objek pembahasan. Hasil penelitian menunjukkan bahwa terdapat beberapa tantangan dalam meraih generasi emas seperti faktor lingkungan, moral, sosial, pendidikan, dan rezeki yang halal, sehingga implementasi survival strategy of family berdasarkan QS. al-Nisa>’/4:9 mencakup 3 hal utama, Menguatkan keimanan, memperbaiki pendidikan dan menstabilkan perekonomian. Dengan penerapan Survival Strategy ini, diharapkan dapat memberikan panduan bagi keluarga Muslim dalam membangun pondasi yang kokoh berdasarkan nilai-nilai Islam, sehingga generasi mendatang tumbuh dengan keteguhan iman, moral dan etika yang mampu menghadapi tantangan Zaman.